Shrines in a fluid space : the shaping of new holy sites in the Ionian Islands, the Peloponnese and Crete under Venetian rule (14th-16th centuries) - Dermitzaki, Argyri (Mediterranean art histories : studies in visual cultures and artistic transfers from late antiquity to the modern period,, 2022)
"In Shrines in a Fluid Space: The Shaping of New Holy Sites in the Ionian Islands, the Peloponnese and Crete under Venetian Rule (14th-16th Centuries), Argyri Dermitzaki reconstructs the devotional experiences within the Greek realm of the Venetian Stato da Mar of Western European pilgrims sailing to Jerusalem. The author traces the evolution of the various forms of cultic sites and the perception of them as nodes of a wider network of the pilgrims' 'holy topography'. She scrutinises travelogues in conjunction with archaeological, visual and historical evidence and offers a study of the cultic phenomena and sites invested with exceptional meaning at the main ports of call of the pilgrims' galleys in the Ionian Sea, the Peloponnese and Crete"--